UI UX DESIGN: SENI KERAJINAN YANG MELIBATKAN PENGALAMAN DIGITAL DALAM MENINGKATKAN LOYALITAS PELANGGAN - Sholaihah, Lutfiah Anisa; Adrian, Rian (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2024)
UI UX Design has become a key factor in creating an engaging and satisfying user experience in today's digital era. It is well known that a good user experience can contribute to increased customer loyalty. This study aims to investigate the role of UI UX Design in increasing customer loyalty and describe how this craft involves digital experiences. This research involved a comprehensive literature review and case studies to explore best practices in UI UX Design. In this study, UI refers to the user interface, while UX refers to the overall user experience in interacting with digital service products. The results of this study indicate that a good UI UX Design can help increase customer loyalty by creating an interesting, intuitive and attractive experience. This research also illustrates that craft in UI UX Design involves collaboration between graphic designers, web developers, and UX experts. A design process that involves deep understanding of user needs, mapping the user journey, and continuous testing and iteration is an important step in creating a great experience.